Password policy purgatory - FARRELL, STEPHEN (IEEE, 2008)
IT system users, (all of us), and administrators, (increasingly large numbers of us), must all manage some passwords. In this article, the author reviews some issues related to password policies and concludes that managing passwords, in any sensible manner, is becoming more and more of a nuisance for users, a factor that should be to the forefront when administrators are creating password policies.
PUBLISHED
Keywords: authorisation